Coffee consumption and NAFLD: a community based study on 1223 subjects. (December 2015) - Graeter, Tilmann; Niedermayer, Pia; Mason, Richard; Oeztuerk, Suemeyra; Haenle, Mark; Koenig, Wolfgang; Boehm, Bernhard; Kratzer, Wolfgang
Abstract Background Objective of the present cross-sectional study was to investigate the impact of caffeine consumption on fatty liver and serum alanine aminotransferase (ALT) concentrations in a random population sample. Methods All subjects (n = 1452; 789 women, 663 men; average age 42.3 ± 12.8 years) underwent ultrasonographic examination of the liver and completed a standardized questionnaire regarding personal and lifestyle data, in particular relating to coffee consumption and past medical history. In addition, anthropometric data were documented and laboratory examinations performed. Statistical interpretation of the data was performed descriptively and by means of bivariate and multivariate analysis. Results Data of the present study demonstrated a significant association between hepatic steatosis male gender (p < 0.0001), advanced age (p < 0.0001) and elevated body-mass index (BMI; p < 0.0001). No association between caffeine consumption and fatty liver was identified. An association between caffeine consumption and elevated serum ALT concentrations was not identified. Conclusions The findings of the present study provide no evidence for an association between caffeine consumption and either the prevalence of hepatic steatosis or serum ALT concentrations.